Undergraduate Students’ Understanding of Fabricated Information on Social Media Platforms - Fidelis, Antidius (University of Dar es Salaam Library Journal, 2025)
Undergraduate students, who are heavy social media users, are more vulnerable to this information than any other group. For this reason, this study sought to uncover these students’ understanding of fabricated information on social media. To study this topic, a cross-sectional descriptive research design was applied. The study employed a survey to collect data from 354 undergraduate students at two universities in Tanzania. To analyse the data and derive descriptive statistics (frequencies and crosstabulations), the study used IBM Statistical Product for Service Solutions (SPSS) version 21. The study has revealed that undergraduate students had inadequate knowledge of fabricated information on social media. The study has also shown that a lack of training and awareness programs on types of fabricated information is related to the inadequacy of knowledge of this information among university students. The study has also revealed the main types of fabricated information, which are fabricated information against individuals and the government. To reduce the prevalence of this information on social media, training programs must be developed and implemented to raise awareness and understanding of the concept of fabricated information, its impact, and mitigation mechanisms. https://dx.doi.org/10.4314/udslj.v20i1.7